1919
DOI: 10.1084/jem.30.3.241
|View full text |Cite
|
Sign up to set email alerts
|

The Oxygen and Carbon Dioxide Content of Arterial and of Venous Blood in Normal Individuals and in Patients With Anemia and Heart Disease

Abstract: The oxygen and carbon dioxide content of the blood in man, both in normal and in pathological conditions, has been studied but little, although the close relation of variations in the blood gases to alterations in the respiratory and circulatory mechanisms and to the blood flow has long been recognized. The difficulties of gas analysis upon small quantities of blood and in the technique of collection of samples have rendered the data hard to obtain and the reports in the literature scanty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1923
1923
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(19 citation statements)
references
References 4 publications
2
17
0
Order By: Relevance
“…These data may be compared with those of Harrop (30) who in 1919 measured 02 and CO2 A-V differences. Calculation of R.Q.…”
Section: A-v Differencesmentioning
confidence: 99%
“…These data may be compared with those of Harrop (30) who in 1919 measured 02 and CO2 A-V differences. Calculation of R.Q.…”
Section: A-v Differencesmentioning
confidence: 99%
“…Lundsgaard (1918) observed increased utilization in all individuals with congestive failure and in "compensated" patients when the rhythm was markedly irregular. Harrop (1919) found that the arteriovenous oxygen differ-261 ence of blood drawn from the arm was usually greater when failure was present than when it was absent. On the other hand, Eppinger, von Papp, and Schwarz (1924) frequently found normal or low values for oxygen utilization in their patients with congestive failure.…”
Section: Methodsmentioning
confidence: 98%
“…There was, however, pioneering work done that provided the foundation for today's knowledge of the pathophysiology of cardiac cachexia. Some of the current theories have their roots in the work that was done decades ago (►Table1), like for instance studies on hypoxia [16], subacute inflammation in HF [17] or upregulated sympathetic activation [18].…”
Section: Pioneering Studiesmentioning
confidence: 99%
“…The subject of cellular hypoxia became a focus of metabolic research already at the beginning of the 20th century. First blood gas analyses were reported as early as 1919 [16], and in 1923 it was observed in studies at high altitudes that in thin air, study subjects would involuntarily lose weight [44]. Evidence for reduced tissue oxygen supply came mostly from indirect observations like increased erythropoietic activity and elevated lactate production.…”
Section: Pioneering Studiesmentioning
confidence: 99%